Analisis Pemasaran Jagung Manis di Subak Delod Sema Desa Kesiman Petilan Kecamatan Denpasar Timur Kota Denpasar - I MADE SANATHANA DHARMA; KETUT BUDI SUSRUSA; PUTU UDAYANI WIJAYANTI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Marketing Analysis of Sweet Corn Produced by Farmers of Subak Delod Sema, Kesiman Petilan Village, East Denpasar District, Denpasar City Sweet corn is an agricultural commodity that has the potential to provide high profits if it is cultivated effectively and efficiently. This study aims to determine the institutional, function, channel and marketing efficiency of sweet corn that are cultivated by farmers in Subak Delod Sema, Kesiman Petilan Village, East Denpasar District, Denpasar City. The number of respondents in this study is 35 out of 177 farmers that was determined by using the Slovin method. The results show that on average, to market their products, farmers sell their sweet corn through two channels, namely (1) farmer producers - collectors - consumers; (2) farmer producers - collectors - retailers (market) - consumers. The results show that not all marketing agencies in these marketing channels perform marketing functions. Both marketing channels can be said to be efficient when viewed from the farmer's share. The marketing margin value is Rp. 400, - / seed for marketing channel I and Rp. 600, - / seed for marketing channel II.